Effect of interval versus continuous training on cardiorespiratory and mitochondrial functions: relationship to aerobic performance improvements in sedentary subjects - Daussin, Frédéric N; Zoll, Joffrey; Dufour, Stéphane P; Ponsot, Elodie; Lonsdorfer-Wolf, Evelyne; Doutreleau, Stéphane; Mettauer, Bertrand; Piquard, François; Geny, Bernard; Richard, Ruddy (American journal of physiology. Regulatory, integrative and comparative physiology, 2008)
The goal of the study was to determine the effects of continuous (CT) vs. intermittent (IT) training yielding identical mechanical work and training duration on skeletal muscle and cardiorespiratory adaptations in sedentary subjects. Eleven subjects (6 men and 5 women, 45 +/- 3 years) were randomly assigned to either of the two 8-wk training programs in a cross-over design, separated by 12 wk of detraining. Maximal oxygen uptake (Vo2max) increased after both trainings (9% with CT vs. 15% with IT), whereas only IT was associated with faster Vo2 kinetics (tau: 68.0 +/- 1.6 vs. 54.9 +/- 0.7 s, P < 0.05) measured during a test to exhaustion (TTE) and with improvements in maximal cardiac output (Qmax, from 18.1 +/- 1.1 to 20.1 +/- 1.2 l/min; P < 0.01). Skeletal muscle mitochondrial oxidative capacities (Vmax) were only increased after IT (3.3 +/- 0.4 before and 4.5 +/- 0.6 micromol O2 x min(-1) x g dw(-1) after training; P < 0.05), whereas capillary density increased after both trainings, with a two-fold higher enhancement after CT (+21 +/- 1% for IT and +40 +/- 3% after CT, P < 0.05). The gain of Vmax was correlated with the gain of TTE and the gain of Vo2max with IT. The gain of Qmax was also correlated with the gain of VO2max. These results suggest that fluctuations of workload and oxygen uptake during training sessions, rather than exercise duration or global energy expenditure, are key factors in improving muscle oxidative capacities. In an integrative view, IT seems optimal in maximizing both peripheral muscle and central cardiorespiratory adaptations, permitting significant functional improvement. These data support the symmorphosis concept in sedentary subjects.